Prevalence of familial hypercholesterolemia in patients presenting with premature acute coronary syndrome. (14th October 2021) - Hauguel, M; Aidan, V; Hergault, H; Beauchet, A; Pepin, M; Prati, G; Pilliere, R; Ouadahi, M; Josseran, L; Rodon, C; Rabes, J P; Dubourg, O; et al.
Abstract: Background: Familial hypercholesterolemia (FH) is a common genetic disorder responsible for premature and severe cardiovascular morbidity and mortality. The FH prevalence in patients who experienced a premature acute coronary syndrome (ACS) ranges from 5 to 50% according to previous studies and no comparison with FH prevalence in general population are available in those studies. Purpose: We aimed to assess the prevalence of clinical FH among patients with premature acute myocardial infarction (MI) (age ≤50 years) and to compare it with FH prevalence in a control population (age ≤50 years), coming from the same population pool. Methods: Patients with diagnosis of premature MI (age ≤50 years) referred to Ambroise Paré hospital from 2014 to 2018 were included. FH prevalence was estimated via the Dutch Lipid Clinic Network score, based on personal and familial history of premature cardiovascular disease, and LDL-cholesterol levels. FH was "possible" with a score between 3 and 5 points, "probable" with a score between 6 and 8 and "definite" with a score >8 and no FH was defined as a score <3. FH prevalence in patients with MI was compared to FH prevalence in a general population (age ≤50 years), coming from the prospective cohort CARVAR 92. Results: Among the 457 patients with premature MI, 220 (48%) patients had no FH, 208 (46%) had a "possible" FH and 29 (6%) had a "probable" or "definite" FH. In the control population, 9900 subjects aged ≤50 years were identified: 9343 (94.37%) had no FH, 541 (5.46%) had a "possible" FH and 16 (0.16%) had a "probable" or "definite" FH. Considering subjects with "probable" or "definite" FH, FH prevalence was 37.5 times greater among patients with premature MI than in control population (p<0.0001). Conclusion: Familial hypercholesterolemia is >30-fold more common in patients referred for premature MI than in general population of the same age, coming from the same population pool. This highlights the need for FH diagnosis after a first episode of MI to enhance lipid-lowering therapy and allow an early identification of family members. Funding Acknowledgement: Type of funding sources: None.